Pedagogical conditions and methods aimed at the formation of musical-auditory representations of future teachers of Musical Arts - Mamykina Anzhelina; Grinchenko Alla (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2020)
The article is devoted to the phenomenon of auditory representations, their content, compliance with musical content, formation, tuning and implementation in the performance process of the future teacher during piano training. The purpose of the article is to substantiate the pedagogical conditions and develop the methods aimed at forming of the future music teacher’s musical-auditory representations. The goal is realised through the implementation of relevant tasks using the methods of theoretical research: analysis, synthesis, deduction, systematisation, pedagogical observation. In the article musical-auditory representation is considered as a professional skill of a musician, formed on the basis of the understanding of semantics – semantic units of musical language, which facilitates the qualitative reproduction of artistic and figurative content and maximum efficiency of musician’s own performance process in creation of artistic-pedagogical and performing interpretations. The list of the skills acquired by the applicant during the formation of auditory perceptions is specified, namely: analytical (to identify and understand the symbolism of musical language; its genre and style) (compare semantic constructs of different musical directions); reflexive, figurative-auditory and sensorimotor. The pedagogical conditions for the formation of auditory representations are offered: gradual expansion of a musical thesaurus in the course of the profession-centred training; stimulating auditory perception by recognising and understanding the elements of musical language; the direction of musical-perceptual experience on the coordination of auditory representations with the sign-semantic context of the performed works. In accordance with the defined conditions, a number of methods have been developed: comparative textual analysis; figurative and auditory analysis; perceptual-auditory analysis; associative music model; semantic identification; artistic reincarnation; polytonation expressiveness; tactile-auditory method. Further research involves the development of the future Arts teachers’ auditory perceptions in classes on accompaniment and ensemble playing, taking into account the specifics of these subjects.